Dermoscopic Discoveries in Psoriasis and Seborrheic dermatitis on the scalp and Relationship with Malady Seriousness: The systematic Review and Meta-analysis - Dabukke, Yeyen Jani Sari (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Dermoscopy has regularly been utilized for hair and scalp clutters. Dermoscopic examinations of psoriasis and seborrheic dermatitis injuries yielded  diverse  morphologies. This ponder pointed to examine the value of dermoscopy within the clinical separation of psoriasis  and  seborrheic  dermatitis  on  the  scalp  and  furthermore  to  assess  its  capacity   in deciding illness seriousness. Method: This study using systematic review that search using keyword Psoriasis, Seborrheic Dermatitis and Dermoscopic Findings. Result: After final screening the author analysize 5 articles. As in methods, the author summarize 2 articles. Conclussion: dermoscopy could be a important and easy-to-use device for separating psoriasis and  seborrheic  dermatitis  on  the  scalp  indeed   on   the   off   chance   that   it   doesn’t   have  sufficient  strength  to   determine   malady   seriousness.   In   expansion,   there's   a   few differences and uncertainty concerning phrasing, which can be settled with future thinks about and the foundation of conventional terms.